Uterine Inflammatory Response After Prostaglandin E1 (Misoprostol) Infusion Prebreeding or Immediately After Embryo Flushing in Commercial Donor Mares - Amorim, Gabrielle BAG [UNESP]; Segabinazzi, Lorenzo GTM; Oliveira, Odilon M [UNESP]; Perecmanis, Simone; Arruda, Rodrigo; Canisso, Igor F. (Elsevier, 2022)
Misoprostol, a synthetic PGE1, is becoming a common therapy for mares with suspected uterine tube obstruction. Recently, there have been concerns that uterine administration of misoprostol induces exacerbated uterine inflammation; however, this has not been critically evaluated. This study aimed to assess the inflammatory response and potential systemic reactions after uterine administration of misoprostol, either during prebreeding or immediately after postembryo flushing. Privately owned embryo donor mares (n = 11) were randomly assigned in a crossover design to receive misoprostol (3 mL +200 µg) or sham (3 mL of lactate Ringer's solution) infusions, bilaterally deposited via deep-horn, at least 72 hours prebreeding (experiment 1) or immediately after embryo flushing (experiment 2). Each mare had one cycle for misoprostol and sham in both experiments and a breeding cycle (no sham or misoprostol) between experiments. Uterine edema, fluid accumulation, and the number of uterine PMN were assessed before each infusion and then daily for 72 hours. Uterine lavage was performed the day after each infusion across groups and experiments. Ovulation was hastened with a GnRH agonist and confirmed at 24 hour-intervals. Mares were bred with semen from one of six stallions per owner's choice. Embryo flushing was performed 8 to 9 days postovulation. In either experiment, misoprostol did not affect uterine edema or fluid accumulation (P > .05). However, both the sham and misoprostol infusions increased the number of PMN up to 48 hours postinfusion in both experiments. Embryo recoveries were similar between sham (45%, 5/11) and misoprostol cycles in experiments 1 (45%, 5/11; P > .05) and 2 (sham, 68%, 7/11; misoprostol, 45%, 5/11; P > .05). In conclusion, misoprostol did not induce exacerbated uterine inflammation in mares or systemic adverse reactions when infused prebreeding or immediately after embryo flushing.
Keywords: Endometritis; Equine; Infertility; PGE; Uterine tube